2007
DOI: 10.1111/j.1600-0404.2007.00877.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effect of intravenous immunoglobulin on anti-MuSK antibody-positive myasthenia gravis

Abstract: Anti-muscle-specific receptor tyrosine kinase (MuSK) antibody-positive myasthenia gravis (MG) patients show various responses to conventional immunosuppressive treatment and some patients are resistant to these therapies. We report a 50-year-old Japanese man with anti-MuSK antibody-positive MG, who showed no or poor response to various therapies, including plasmapheresis, corticosteroid, and tacrolimus. The patient was then treated with intravenous immunoglobulin (IVIG), and showed a good response that persist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
0
6
0
2
Order By: Relevance
“…Steroids alone ( 13 ) or combined with an immunosuppressant, such as azathioprine ( 14 ), cyclosporine ( 15 ), or tacrolimus ( 16 ), are generally effective for treating MuSK-MG. Indeed, Shibata-Hamaguchi et al reported that patients treated with IVIg showed good outcomes over a long period of time ( 5 ). However, MuSK-MG patients show variable responses to such conventional immunosuppressive treatment, and some are resistant to these therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Steroids alone ( 13 ) or combined with an immunosuppressant, such as azathioprine ( 14 ), cyclosporine ( 15 ), or tacrolimus ( 16 ), are generally effective for treating MuSK-MG. Indeed, Shibata-Hamaguchi et al reported that patients treated with IVIg showed good outcomes over a long period of time ( 5 ). However, MuSK-MG patients show variable responses to such conventional immunosuppressive treatment, and some are resistant to these therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-MuSK antibodies mainly belong to the immunoglobulin-G4 (IgG4) subclass, which decrease the clustering of AChR, resulting in abnormalities in electrophysiological neuromuscular junctions ( 4 ). Anti-MuSK antibody-positive MG (MuSK-MG) patients show various responses to cholinesterase inhibitor, oral high-dose daily prednisolone (PSL), azathioprine, cyclosporin A, mycophenolate mofetil, intravenous immunoglobulin (IVIG) ( 5 ), rituximab ( 6 ), and plasma exchange (PE) ( 7 ) but respond poorly to thymectomy ( 8 - 11 ). Although conventional immunosuppressants are effective in most MuSK-MG patients, some patients respond poorly or are unable to continue these therapies due to adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…In our and other clinicians’ experience, the usefulness of plasma‐exchange in patients with frequent disease relapses appears to be significantly limited by the short‐lasting effect. In these cases, in spite of concomitant immunosuppressive treatment, the clinical response to plasma exchange tends to become shorter with time, sometimes lasting no longer than two weeks 11–42 . On the other hand, three Japanese patients previously unresponsive to thymectomy, steroids, and tacrolimus, and dependent on plasma exchange, achieved long‐term improvement with IVIG treatment 41,42 …”
Section: Management Of Refractory Diseasementioning
confidence: 99%
“…Pueden estar ausentes o a bajos títulos en el 50% de la MG ocular o infantil. En las formas seronegativas pueden detectarse IgG anti-MuSK, anticuerpos dirigidos a una proteína intrínseca de membrana, tirosina quinasa músculo-específica, que pueden llegar a detectarse, según las series en el 34-71% de las MG generalizada seronegativas y configuran un subgrupo clínico, evolutivo y de respuesta terapéutica diferente a aquellas en las que el antígeno es el receptor de la acetil-colina 18,19 . Existen dos tipos de tratamiento 20 , el sintomático dirigido a prolongar la acción de la acetil-colina en la membrana postsinápti-ca y mejorar así la transmisión neuromuscular y el etiopatogénico o modificador de la historia natural de la enfermedad que engloba la timectomía, los agentes inmunosupresores e inmunomoduladores a corto plazo como la plasmaféresis o las IgIv.…”
Section: Miastenia Gravis (Mg)unclassified